Complicity without connection or communication - Barr, Abigail; Michailidou, Georgia (Elsevier, 2017)
We use a novel laboratory experiment involving a die rolling task embedded within a coordination game to investigate whether complicity can emerge when decision-making is simultaneous, the potential accomplices are strangers and neither communication nor signaling is possible. Then, by comparing the behavior observed in this original game to that in a variant in which die-roll reporting players are paired with passive players instead of other die-roll reporters, while everything else is held constant, we isolate the effect of having a potential accomplice on the likelihood of an individual acting immorally. We find that complicity can emerge between strangers in the absence of opportunities to communicate or signal and that having a potential accomplice increases the likelihood of an individual acting immorally.